[OP.5C.09] AGE-RELATED TREATMENT BENEFIT OF AN ACE INHIBITOR ON CARDIOVASCULAR EVENTS: THE EMERGING ROLE OF BRADYKININ. (September 2016) - Brugts, J.; Ferrari, R.
Abstract : Objective: Angiotensin-converting enzyme inhibitors are known to provide significant benefits on cardiovascular event reduction and survival by regulating the balance between bradykinin and angiotensin II. We performed a combined analysis of three randomized trials including the ACE inhibitor perindopril to determine the variability of the response to treatment depending on age. Design and method: In the ADVANCE, EUROPA and PROGRESS trials, we analyzed the age-dependent of perindopril on the composite endpoint of cardiovascular mortality, nonfatal myocardial infarction and stroke compared to placebo with multivariate Cox regression. In the PERTINENT study, a subgroup of patients of the EUROPA trial for whom blood samples were collected after one year of treatment, we analyzed the effect of perindopril treatment on plasma angiotensin II and bradykinin levels in age strata. Results: Among the 29 463 patients included in the trials, mean age was of 63 years with a large representation of populations below 60 years old (9684 patients). Overall, the relative risk of cardiovascular death, nonfatal myocardial infarction and stroke was significantly reduced in patients receiving perindopril (HR 0.82, 95% CI: 0.76–0.88). Interestingly, the risk reduction was numerically larger in the younger groups of patients below 60 years: -28% (HR 0.72, 95% CI: 0.62–0.83), -16% in patients between 60 to 70 years (HR 0.84, 95% CI: 0.75–0.93) and above 70 years -12% (HR 0.88, 95% CI 0.78–0.98), P for interaction 0.07. In the EUROPA trial, plasma dosages (n = 87) indicated that perindopril decreased angiotensin II significantly compared to placebo (12.26 pg/ml vs 14.66 pg/ml, p = 0.046) and increased bradykinin concentration (17.75 pg/ml vs 12.25 pg/ml, p = 0.0002). In the group of patients below 60 years, angiotensin II concentration was not further decreased (13.39 pg/ml) but bradykinin increase was larger (19.05 pg/ml, p = 0.0057 vs placebo) compared to other groups (17.18 pg/ml for 60–65 years and 16.31 pg/ml for > 65 years). Conclusions: Perindopril treatment is associated with a significant reduction of major CV events which may be more pronounced in younger patients. Based on these preliminary findings, we hypothesize that the enhanced effect may be related to the preservation of bradykinin in younger populations.